100 Outcomes for inpatients with chronic liver disease, is there a need for better palliative care provision?. Issue Volume 11: Issue (2021)Supplement 1 (16th March 2021) - Fox, Hannah; Hendicott, Eleanor; Haldar, Debashis; Corbett, Chris; Coop, Hazel
Abstract : Background: Liver disease is the third largest cause of UK death in working age people and is prevalent locally. Early access to palliative care is associated with better quality of life and fewer hospital admissions. This study explores prognosis of inpatients with chronic liver disease (CLD) and their interaction with palliative care. Methods: New Cross Hospital inpatients with CLD, without malignancy, were discussed at the weekly liver Multidisciplinary Team (MDT) meeting (2014 to 2016) and followed up until 2020. Data were retrospectively collected using written and electronic records to determine baseline factors, liver disease severity, follow up and intervention, and analysed for timepoint analyses of death. Results: 112 patients data were analysed. The mean age was 55. 86% (96) had alcohol related liver disease. Other primary aetiologies included non-alcoholic fatty liver disease, cholestatic liver disease and drug-induced liver disease. 51% (57) died within a year of MDT, at least a further 21% (23) died during follow up. 58% (42) with Child-Pugh C grading died within a year of MDT, a further 18% (13) died during follow up. 3 patients went on to liver transplantation. Child-Pugh C grading was 74% sensitive for identifying those who will die within 1 year, but only 42% specific. Child-Pugh B or C was 100% sensitive for death within 1 year, but only 9% specific. 47% with Child-Pugh C, 37% of Child-Pugh B and 20% of Child-Pugh A were known to specialist palliative care team (SPCT). 56% of deceased patients were known to SPCT. Conclusions: This data confirms the poor prognosis of inpatients with CLD and demonstrates a need for greater integration of advance care planning principles and palliative care support. Further research is needed to assess which interventions would be beneficial and acceptable to these patients, or how we identify those who would most benefit.